Che Guevara's face : how a Cuban photographer's image became a cultural icon - Smith-Llera, Danielle, 1971- (Captured world history, 2017)
"Discusses the iconic photograph of revolutionary Che Guevara taken in 1960 by Cuban photographer Alberto Korda"--